Colon cancer patients with mismatch repair deficiency are more likely to present as acute surgical cases - Gkekas, Ioannis; Novotny, Jan; Kaprio, Tuomas; Beilmann-Lehtonen, Ines; Fabian, Pavel; Edin, Sofia; Strigård, Karin; Svoboda, Tomas; Hagström, Jaana; Barsova, Lucie; Jirasek, Tomas; Haglund, Caj; et al. (European journal of cancer, 2021)
BACKGROUND: The effect of the genetic imprint on the emergency presentation of colon cancer remains unclear. The disparity between tumours evolving along different carcinogenetic pathways has not been studied systematically. This retrospective multicenter cohort study evaluates the association between mismatch repair status and the risk for acute surgery of colon cancer. PATIENTS AND METHODS: A retrospective multicenter cohort study including in total 870 patients from three different countries. Scandinavian cohort (Finland and Sweden), including a total of 412 patients operated between January 1, 1995 and December 31, 2010, was validated against a cohort from the Czech Republic, including a total of 458 patients, operated between January 1, 2018 and December 31, 2019. The proficiency or deficiency of mismatch repair was determined by immunohistochemistry. Primary outcome was the risk for acute colon cancer surgery given as the Odds Ratio (OR) in the univariable and multivariable analyses. Acute colon cancer surgery was defined as surgery performed during the same hospital admission as when the diagnosis of colon cancer was made. RESULTS: Of the 870 patients (399 females [46%]) included in the analyses, median age at surgery was 69 [interquartile range, 61-76] years, deficient Mismatch Repair (dMMR) status was found in 190 patients (22%), and 179 patients (21%) underwent acute surgery during the same hospital admission as when the diagnosis of colon cancer was made. In the Scandinavian cohort, a significant association between dMMR status and acute surgery was seen in both the univariable (OR 1.82, 95% CI 1.11-3.02, P = 0.017) and the multivariable (OR = 2.21, 95% CI 1.28-3.95, P = 0.005) analyses. This was confirmed in the Czech validation cohort in both the univariable (OR = 1.94, 95% CI 1.09-3.26, P = 0.022) and the multivariable (OR = 1.77, 95% CI 1.15-3.18, P = 0.021) analyses. CONCLUSION: This multicenter study reveals a strong association between acute colon cancer surgery and dMMR tumour status.
Keywords: nádory tračníku; dědičné nádorové syndromy; Aged; Aged, 80 and over; Neoplasm Staging; Retrospective Studies; lidé středního věku; senioři; nádory mozku; lidé; staging nádorů; Adult; Brain Neoplasms; Middle Aged; dospělí; Female; senioři nad 80 let; kolorektální nádory; Male; ženské pohlaví; Colorectal Neoplasms; Neoplastic Syndromes, Hereditary; Humans; mužské pohlaví; Colonic Neoplasms; retrospektivní studie